The Relation between Intellectual Property Management and Firm Performance of Vietnamese Firms in the Information and Communication Technology Industry (ICT) - Thi Thu Ha, Le; Nhu Ngoc, Nguyen; Thi Dai Trang, Luong (VNU Journal of Science: Policy and Management Studies; Vol 38 No 1DO - 10.25073/2588-1116/vnupam.4340, 2022)
Information and Communication Technology (ICT) is a core of the knowledge economy and among the most potential industries of Vietnam for the upcoming years. As in an industry with a high content of innovation and intellectual properties, ICT firms are required to have a wise intellectual property strategy to assure their preposition and sustainable development. Meanwhile, studies on intellectual property of Vietnam have hardly touched upon the management perspective, especially the firm management perspective. Therefore, this study examines the impacts of intellectual property management on firm performance in ICT industry of Vietnam. Intellectual property management is assessed through four levels, namely Awareness, Registration, Exploitation and Management, and Protection. Four measurements of firm performance are profitability, revenue growth, market share and the ability to maintain stable jobs and benefits for employees. Data obtained from 122 Vietnamese ICT firms indicates that each level of intellectual property management has a positive impact on firm performance. The findings provide a scientific basis for improving intellectual property management of ICT firms and Vietnamese firms in general. Keywords Intellectual property, intellectual property management, firm performance, Information and Communication Technology, ICT. References [1] Ocean Tomo, Annual Study of Intangible Asset Market Value, https://www.oceantomo.com/intangible-asset-market-value-study/, 2020 (accessed on: July 28th, 2021). [2] O. Granstrand, The Economics and Management Of Intellectual Property, Edward Elgar, Cheltenham, Northampton, 2000. [3] K. Idris, Intellectual Property - A Power Tool for Economic Growth, World Intellectual Property Organization, 2003. [4] K. Carlaw, L. Oxley, P. Walker, D. Thorns, M. Nuth, Beyond the Hype: Intellectual Property and The Knowledge Society/Knowledge Economy, Journal Of Economic Surveys, Vol. 20, No. 4, 2006, pp. 633-690, https://doi.org/10.1111/j.1467-6419.2006.00262.x. [5] J. Paasi, T. Luoma, K. Valkokari, N. Lee, Knowledge and Intellectual Property Management In Customer–Supplier Relationships, International Journal of Innovation Management, 2010, pp. 195-221, https://doi.org/10.1142/9781786343512_0010. [6] P. Sullivan, Profiting from Intellectual Capital, Journal of Knowledge Management, Vol. 3, No. 2, 1999, pp. 132-143, https://doi.org/10.1108/13673279910275585. [7] W. Fisher III, F. O. Gee, Strategic Management Of Intellectual Property: An Integrated Approach, California Management Review, 2013, pp. 157-183, https://doi.org/10.1525/cmr.2013.55.4.157. [8] D. Spruson, N. Ferguson, Intellectual Property Management A Practical Guide for Electrical and Electronics Related Industries, http://www.spruson.com/wpcontent/uploads/2014/01/IP_Management_Guide_lowres.pdf/, 2007, (accessed on: June 14th, 2021). [9] J. Kitching, R. Blackburn, Intellectual Property Management In The Small And Medium Enterprises, SME, Journal of Small Business and Enterprise Development, Vol. 5, No. 4, 1998, pp. 327-355, https://doi.org/10.1108/EUM0000000006797. [10] S. Papaioannou, S. Dimelis, Information Technology as a Factor of Economic Development: Evidence from Developed and Developing Countries, Economic Innovation and New Technology Journal, Vol. 16, No. 3, 2007, pp. 179-194, https://doi.org/10.1108/EUM0000000006797. [11] C. Freeman, C. Perez, Structural Crises of Adjustment, Business Cycles and Investment Behaviour, in Dosi, Technical Change and Economic Theory, 1988, pp. 38-66. [12] A. Saheer, C. Westrup, Jordan and ICT‐led Development: Towards A Competition State?, Information Technology & People, Vo. 16, No. 1, 2003, pp. 93-110, https://doi.org/10.1108/09593840310463032. [13] K. Kraemer, J. Dedrick, J, Payoffs from Investments in Information Technology: Lessons from the Asia–Pacific Region, World Development, Vol. 22, No. 12, 1994, pp. 1921-1931, https://doi.org/10.1016/0305-750X(94)90183-X. [14] S. Newell, M. Bresnen, L. Edelman, H. Scarbrough, J. Swan, Sharing Knowledge Across Projects, Management Learning, Vol. 37, No. 2, 2006, pp. 167-185, https://doi.org/10.1177/1350507606063441. [15] C. O. Duze, Impediments to ICT-led Development in Nigeria: The Case of ICT ‘Illiteracy’ in Universities, Journal of Science and Sustainable Development, Vol. 3, No. 1, 2010, https://doi.org/10.4314/jssdv3i1.67756. [16] M. Ashraf, J. Hanisch, P. Swatman, ICT Intervention in the Chandanbari Village of Bangladesh: Results from a Field Study, Information Systems Frontiers, Vo. 11, No. 2, 2009, pp. 155-166, https://doi.org/10.1007/s10796-008-9133-0. [17] S. Comino, F. M. Manenti, N. Thumm, Intellectual Property and Innovation in Information and Communication Technology (ICT), European Commission, 2015. [18] V. Ly, The Saigon Times, Information Technology on the list of hundred-billion-dollar companies, https://www.thesaigontimes.vn/312595/cong-nghe-thong-tin-vao-danh-sach-nganh-cong-nghiep-tram-ti-do-la.html/, 2020 (accessed on: July 27th, 2021). [19] Vietnam Report, Announcement of top 500 Fastest Growing Enterprises in Vietnam, https://vietnamreport.net.vn/Cong-bo-Top-500-Doanh-nghiep-tang-truong-nhanh-nhat-Viet-Nam-2021-9665-1006.html/, 2021, (accessed on: July 20th, 2021). [20] H. C. Palmqvist, B. Sandberg, M. U. Maija, Intellectual Property Rights in Innovation Management Research: A Review, Technovation, Vol. 32, 2012, pp. 505-512, https://doi.org/10.1016/j.technovation.2012.01.005. [21] The United State Trade Representative, 2021 Special 301 Report, https://ustr.gov/sites/default/files/files/reports/2021/2021%20Special%20301%20Report%20(final).pdf/, 2021 (accessed on: July 28th, 2021). [22] T. D. Binh, Improving the Effectiveness of Intellectual Property Management and Enforcement in Thanh Hoa Province Based on Linking Information Sources, Vietnam National University, Doctoral dissertation, 2011 (in Vietnamese). [23] N. V. Bay, Intellectual Property Strategy to 2030: Comprehensive and Effective Development of Vietnam’s Intellectual Property System, Vietnam Journal of Science and Technology, Vol. 10A, No. 8, 2019, pp. 8-10 (in Vietnamese). [24] T. T. Lan, Establishing a Model for Intellectual Property Management at Vietnam Academy of Science and Technology, Vietnam Journal of Science and Technology, Vol. 12A, No. 33, 2019 (in Vietnamese). [25] T. V. Khanh, some Features of Intellectual Property Activities in Universities, http://113.190.240.60:8080/phamquangquyen/bitstream/123456789/642/1/36_3.pdf/, 2014 (in Vietnamese). [26] M. G. Kirkpatrick, Intellectual Assets and Value Creation: Implications for Corporate Reporting, Paris, Organization for Economic Co-operation and Development, 2006. [27] Vietnam National Assembly, Intellectual Property Law 07/VBHN-VPQH, 2019. [28] H. Goldrian, The Management and Exploitation oOf Intellectual Property Rights by Small and Medium Sized Industries; Lecture to WIPO Academy, Geneva October 4th-15th, 1993. [29] H. Chesbrough, Open Business Models: How to Thrive in the New Innovation Landscape, Harvard Business School Press, 2006. [30] J. S. Davis, S. S. Harrison, Edison in the Boardroom: How Leading Companies Realize Value From Their Intellectual Assets, Wiley Publishers, 2001. [31] W. Croft, Typology and Universals, The Handbook of Linguistics, 2nd ed. Oxford: Wiley Blackwell, 2017, pp. 39-56, https://doi.org/10.1002/9781119072256. [32] N. Thumm, Strategic Patenting In Biotechnolog, Technology Analysis & Strategic Management, Vol. 16, No. 4, 2004, pp. 529-538, https://doi.org/10.1080/0953732042000295829. [33] T. Jokela, M. Siponen, N. Hirasawa, J. Earthy, A Survey of Usability Capability Maturity Models: Implications for Practice and Research, Behaviour & Information Technology, Vol. 25, No. 3, 2006, pp. 263-282, https://doi.org/10.1080/01449290500168079. [34] Y. K. Gibb, S. Blili, Small Business and Intellectual Asset Governance: An Integrated Analytical Framework, GSTF Journal on Business Review Vol. 2, No. 2, 2012, https://doi.org/10.5176/2010-4804-2.2.211. [35] S. Kern, R. V. Reekum, The use of Patents in Dutch Biopharmaceutical SME: A Typology for Assessing Strategic Patent Management Maturity, in New Technology-based Firms in the New Millennium, Emerald Group Publishing Limited, 2012, https://doi.org/10.1108/S1876-0228(2012) 0000009012. [36] K. Kjaer, Supply and Demand of Intellectual Property Rights Services for Small and Medium Sized Enterprises – A gap analysis, The Danish Patent and Trademark Office, 2009, http://ipeuropaware.old.ogpi.ua.es/public_documents/Gap%20Analysis%20-%20IP%20support%20services.PDF (accessed on: July 28th, 2021). [37] S. Tangen, Demystifying productivity and performance, International Journal of Productivity and Performance Management, 2005, https://doi.org/10.1108/17410400510571437. [38] A. C. Hax, N. S. Majluf, Strategic Management: an Integrative Perspective, in Strategic Management: An Integrative Perspective, 1984, pp. 468-468. [39] A. A. Atkinson, J. H. Waterhouse, R. B. Wells, A Stakeholder Approach to Strategic Performance Measurement, MIT Sloan Management Review, Vol. 38, No. 3, 1997, pp. 25. [40] K. H. T. Keh, N. T. T. Mai, H. P. Ng, The effects of Entrepreneurial Orientation and Marketing Information on the Performance of SMEs, Journal of Business Venturing, 2007, pp. 592-611, https://doi.org/10.1016/j.jbusvent.2006.05.003. [41] G. B. Murphy, S. K. Callaway, Doing Well and Happy About it? Explaining Variance in Entrepreneurs' Stated Satisfaction with Performance, New England Journal of Entrepreneurship, 2004, https://doi.org/10.1108/NEJE-07-02-2004-B003. [42] D. Koufopoulos, V. Zoumbos, M. Argyropoulou, J. Motwani, Top Management Team and Corporate Performance: A study of Greek Firms, Team Performance Management, 2008, https://doi.org/10.1108/13527590810912322. [43] J. Wiklund, The Sustainability of the Entrepreneurial Orientation–Performance Relationship, Entrepreneurship Theory and Practice, 1999, https://doi.org/10.1177%2F104225879902400103. [44] J. E. Butler, H. T. Keh, W. Chamornmarn, Information Acquisition, Entrepreneurial Performance and the Evolution of Modern Thai Retailing, Journal of Asian Business, 2000. [45] R. Tajvidi, A. Karami, The effect of Social Media on Firm Performance, Computers in Human Behaviors, 2017, https://doi.org/10.1016/j.chb.2017.09.026. [46] G. B. Murphy, J. W. Trailer, R. C. Hill, Measuring Performance in Entrepreneurship Research, Journal of Business Research, 1996, https://doi.org/10.1016/0148-2963(95)00159-X. [47] A. K. Gupta, V. Govindarajan, Business Unit Strategy, Managerial Characteristics, and Business Unit Effectiveness at Strategy Implementation, Academy of Management Journal, 1984, https://doi.org/10.5465/255955. [48] A. Neely, M. Gregory, K. Platts, Performance Measurement System Design: A Literature Review and Research Agenda, International Journal of Operations & Production Management, 2005, https://doi.org/10.1108/01443579510083622. [49] A. Arora, A. Nandkumar, Insecure Advantage? Markets for Technology and the Value of Resourcesf Entrepreneurial Ventures, Strategic Management Journal, Vol. 33, No. 3, 2012, https://doi.org/10.1002/smj.953. [50] D. H. Hsu, R. H. Ziedonis, Resources as Dual Sources of Advantage: Implications for Valuing Entrepreneurial-Firm Patents, Strategic Management Journal, Vol. 34, No. 7, 2013, pp. 761–781, https://doi.org/10.1002/smj.2037. [51] ] R. J. Mann, Do Patents Facilitate Financing in the Software Industry?, Texas Law Review, Vol. 83, No. 4, 2005, pp. 961-1030. [52] R. J. Mann, T. W. Sager, Patents, Venture Capital, and Software Start-ups, Research Policy, Vol. 36, No. 2, 2007, pp. 193-208, https://doi.org/10.1016/j.respol.2006.10.002. [53] K. W. Willoughby, How do Entrepreneurial Technology Firms Really Get Financed, and What Difference Does It Make?, International Journal of Innovation and Technology Management, Vol. 5, No. 1, 2008, https://doi.org/10.1142/S0219877008001266. [54] D. Suh, J. Hwang, An Analysis of the Effect of Software Intellectual Property Rights on the Performance of Software Firms in South Korea, Technovation, 2010, pp. 376-385, https://doi.org/10.1016/j.technovation.2009.08.005. [55] L. Bollen, P. Vergauwen, S. Schnieders, Linking Intellectual Capital and Intellectual Property to Company Performance, Management Decision, 2005, https://doi.org/10.1108/00251740510626254. [56] Y. H. Hsu, W. Fang, Intellectual Capital and New Product Development Performance: The Mediating Role of Organizational Learning Capability, Technological Forecasting and Social Change, Vol. 76, No. 5, 2009, pp. 664-677, https://doi.org/10.1016/j.techfore.2008.03.012. [57] W. Y. Wu, M. L. Chang, C. W. Chen, Promoting Innovation Through The Accumulation of Intellectual Capital, Social Capital, and Entrepreneurial Orientation, R&D Management, Vol. 38, No. 3, 2008, pp. 265-277, https://doi.org/10.1111/1467-9914.00120-i1. [58] C. M. Kalanje, Role of Intellectual Property in Innovation and New Product Development, World Intellectual Property Organization, 2006. [59] D. H. Austin, An Event-Study Approach to Measuring Innovative Output: The Case of Biotechnology, American Economic Review, Vol. 83, No. 2, 1993, pp. 253-258, https://www.jstor.org/stable/2117673. [60] . H. Austin, The Power of Patents, Resources, Vol. 119, 1995, pp. 2-5. [61] W. M. Landes, R. A. Posner, Trademark Law: an Economic Perspective, The Journal of Law and Economics, Vol. 30, No. 2, 1987, pp. 265-309, https://doi.org/10.1086/467138. [62] C. Seethamraju, The Value Relevance Of Trademarks, in Intangible Assets: Values, Measures, and Risks, by J. Hand and B. Lev. (eds.), Oxford University Press, Oxford, 2003. [63] U. Lichtenthaler, H. Ernst, Opening up the Innovation Process: The Role of Technology Aggressiveness, R&D Management, Vol. 39, 2009, pp. 38-54, https://doi.org/10.1111/j.1467-9310.2008.00522.x. [64] P. R. Tomlinson, Co-operative Ties and Innovation: Some New Evidence for UK Manufacturing, Research Policy, Vol. 39, 2010, pp. 762-775, https://doi.org/10.1016/j.respol.2010.02.010. [65] M. Fransman, the New ICT Ecosystem: Implications for Policy And Regulation, Cambridge University Press, 2010. [66] P. Ritala, V. Agouridas, D. Assimakopoulos, O. Gies, Value Creation and Capture Mechanisms in Innovation Ecosystems: A Comparative Case Study, International Journal of Technology Management, Vol. 63, 2013, pp. 244-267, https://doi.org/10.1504/IJTM.2013.056900. [67] K. Laursen, A. Salter, Open for Innovation: The Role of Openness in Explaining Innovation Performance Among UK Manufacturing Firms, Strategic Management Journal, Vol. 27, No. 2, 2006, pp. 131-150, https://doi.org/10.1002/smj.507. [68] P. H. Jensen, E. Webster, Another Look at the Relationship Between Innovationm Proxies, Australian Economic Papers, Vol. 48, No. 3, 2009, pp. 252-269, https://doi.org/10.1111/j.14678454.2009.00374.x. [69] R. H. Pitkethly, Intellectual Property Awareness, International Journal of Technology Management, Vol. 59, No. 3-4, 2012, pp. 163-179, https://doi.org/10.1504/IJTM.2012.047243. [70] R. Berger, Utilisation of Patent Protection in Europe, EPOScript 3, European Patent Office, Munich, 1994. [71] P. K. Urwin, Valuing Brands in the UK Economy, London: Westminster Business School University of Westminster, 2008. [72] A. Arora, A. Fosfuri, A. Gambardella, Markets for Technology and their Implications for Corporate Strategy, Industrial and Corporate Change, 2001, https://doi.org/10.1093/icc/10.2.419. [73] M. D. Beneish, C. R. Harvey, A. Tseng, Unpatented Innovation and Merger Synergies, Review Account Study, 2021, https://doi.org/10.1007/s11142-021-09613-9. [74] O. Gassmann, M. A. Bader, Intellectual Property Management in Inter-firm R&D Collaborations, Taiwan Academy of Management Journal, 2006. [75] M. G. Moehrle, L. Walter, M. Wustmans, Designing the 7D Patent Management Maturity Model – A Capability-based Approach, World Patent Information, Vol. 50, 2017, pp. 27-33, https://doi.org/10.1016/j.wpi.2017.08.003. [76] D. Somaya, Patent Strategy and Management: An Integrative Review and Research Agenda, Journal of Management, Vol. 38, No. 4, 2012, pp. 1084-1114, https://doi.org/10.1177%2F0149206312444447. [77] U. Lichtenthaler, H. Ernst, External Technology Commercialization in Large Firms: Results of a Quantitative Benchmarking Study, R&D Management, 2007, https://doi.org/10.1111/j.14679310.2007.00487.x. [78] J. F. Jr. Hair, R. E. Anderson, R. L. Tatham, W. C. Black, Multivariate Data Analysis (6th ed.), New Jersey: Prentice-Hall, 2006.